Carrier screening for single gene disorders. Issue 2 (April 2018) - Rose, Nancy C.; Wick, Myra
Abstract: Screening for genetic disorders began in 1963 with the initiation of newborn screening for phenylketonuria. Advances in molecular technology have made both newborn screening for newborns affected with serious disorders, and carrier screening of individuals at risk for offspring with genetic disorders, more complex and more widely available. Carrier screening today can be performed secondary to family history-based screening, ethnic-based screening, and expanded carrier screening (ECS). ECS is panel-based screening, which analyzes carrier status for hundreds of genetic disorders irrespective of patient race or ethnicity. In this article, we review the historical and current aspects of carrier screening for single gene disorders, including future research directions.